Laparoscopic repeat surgery for gastro-oesophageal reflux disease: Results of the analyses of a cohort study of 117 patients from a multicenter experience. (April 2020) - Panaro, Fabrizio; Leon, Piera; Perniceni, Thierry; Bianchi, Giorgio; Souche, Francois-Regis; Fabre, Jean Michel; De Blasi, Vito; Azagra, Santiago; Marin, Grégory; Giannandrea, Giusy; Gayet, Brice; Navarro, Francis; et al.
Abstract: Background: Short and long-term outcomes after repeat anti-reflux surgery (RARS) are still debated and generally not considered as satisfying as after primary anti-reflux surgery (PARS). The aim of this study was to evaluate functional outcomes after RARS and risk factors associated to intra-operative and post-operative complications. Methods: This is a multicenter retrospective survey from four European laparoscopic centers. Patients who underwent elective RARS from January 2005 to October 2017 for dysphagia or for persistent reflux disease refractory to medical treatment were analyzed. Data on demographic characteristics, including type and timing of previous operations as well as intra-operative details (surgical technique, type of RARS, conversion to open surgery, prosthetic material placement) were collected. Patients who underwent operations in the emergency setting, interventions mixed with bariatric procedures and PARS performed in other surgical departments were not included in this study. Primary endpoint of this study was to evaluate risk factors associated with intraoperative and postoperative complications. Secondary endpoint was to evaluate clinical outcomes and to identify any possible correlation with clinical and surgical parameters. Results: Among 1662 patients who underwent PARS, failure occurred in 174 (10.5%) patients. Repeat surgery was performed in 117 (7%) patients, after a mean time of 80 months (range 4–315). RARS was carried out laparoscopically in 88% of cases. Prosthetic mesh to reinforce hiatoplasty was used in 22.2% of patients. Intra-operative upper gastro-intestinal tract's injuries occurred in 6 (5.1%) patients. Perioperative mortality was nil and 13 (11.1%) patients experienced postoperative complications. Mean length of hospital stay was 9.6 ± 6.4 days. Based on a multivariable analysis, age >70 years (OR 1.074, C.I.95% 1.018–1.133, p = 0.008) and body mass index (BMI) < 23 (OR 0.172, C.I.95% 0.052–0.568, p = 0.004) were independently associated to postoperative complications. After a mean follow-up time of 36 months (range 6–107), 24 (20.5%) patients presented recurrent symptoms. Based on a multivariable analysis, early onset of dysphagia (OR 3.539, C.I.95% 1.254–9.990, p = 0.017), open approach (OR 4.505, C.I.95% 1.314–15.442, p = 0.016) and the use of prosthetic material (OR 2.790, C.I.95% 0.930–8.776, p = 0.047) were significantly associated to good clinical outcomes. Conclusions: Repeat anti-reflux surgery is a safe and feasible procedure in high-volume centers, with acceptable perioperative outcomes. Long-term results are favorable with a success rate of almost 80%. Advanced age (>70 years) and low BMI (<23 kg/m 2 ) were factor predicting perioperative complications. The use of prosthesis for hiatoplasty was associated to better functional outcomes. Highlights: Repeat anti-reflux surgery is a safe and feasible procedure in high-volume centers. Long-term outcomes can be considered as satisfying as after primary surgery, since it provides a success rate of almost 80%. Advanced age and BMI <23 kg/m 2 were factor negatively impacting postoperative complications. The use of prosthetic materials for hiatoplasty was associated to better functional outcomes.